Correct patterning of the primitive streak requires the anterior visceral endoderm. - Daniel W Stuckey; Aida Di Gregorio; Melanie Clements; Tristan A Rodriguez (PLoS ONE)
Anterior-posterior axis specification in the mouse requires signalling from a specialised extra-embryonic tissue called the anterior visceral endoderm (AVE). AVE precursors are induced at the distal tip of the embryo and move to the prospective anterior. Embryological and genetic analysis has demonstrated that the AVE is required for anterior patterning and for correctly positioning the site of primitive streak formation by inhibiting Nodal activity. We have carried out a genetic ablation of the Hex-expressing cells of the AVE (Hex-AVE) by knocking the Diphtheria toxin subunit A into the Hex locus in an inducible manner. Using this model we have identified that, in addition to its requirement in the anterior of the embryo, the Hex-AVE sub-population has a novel role between 5.5 and 6.5dpc in patterning the primitive streak. Embryos lacking the Hex-AVE display delayed initiation of primitive streak formation and miss-patterning of the anterior primitive streak. We demonstrate that in the absence of the Hex-AVE the restriction of Bmp2 expression to the proximal visceral endoderm is also defective and expression of Wnt3 and Nodal is not correctly restricted to the posterior epiblast. These results, coupled with the observation that reducing Nodal signalling in Hex-AVE ablated embryos increases the frequency of phenotypes observed, suggests that these primitive streak patterning defects are due to defective Nodal signalling. Together, our experiments demonstrate that the AVE is not only required for anterior patterning, but also that specific sub-populations of this tissue are required to pattern the posterior of the embryo.